The preference of high-rise buildings residents toward rooftop garden to promote urban agriculture: a case study of Malaysia - Mohd Yunus, Mohd. Yazid; Jafari, Neda; Nangkula, Utaberta; Ismail, Nor Atiah; Ismail, Sumarni; Jafari, Nastaran (American-Eurasian Network for Scientific Information, 2015)
Nowadays urbanization growing rapidly and also there is a tremendous growth in population which effect the number and height of the building directly. In addition, there has brought about a number of challenges such as greater ambient noise, increased environmental stressors and information overload. High concentration of buildings actually triggers many environmental issues. The instant objective of this research was to examine the preference of high-rise buildings' residents toward rooftop garden to promote urban agriculture. In this research a method presented quantitative -survey questionnaire distributed among of residents in The Sri Putramas 2 condominium in Kuala Lumpur and The Heritage condominium in Selangor. The result is towards recognition of preference to elevate sustainable building and promoting the usage of rooftop gardening residential building. In conclusion most of participants release positive correlation with having rooftop garden in their living area and the outcome of this study is that, rooftop garden as reduce environmental problems. Furthermore, rooftop garden also contribute to the improvement of microclimate.